Characterization of 2D MoS2 and WS2 Dispersed in Organic Solvents for Composite Applications. Issue 32 (29th July 2016) - Delgado, Alberto; Catalan, Jorge A.; Yamaguchi, Hisato; Narvaez Villarrubia, Claudia; Mohite, Aditya D.; Kaul, Anupama B.
ABSTRACT: In this work, we have explored the prospects of MoS2 and WS2, both of which are semiconducting 2D materials, for potential composite applications. In order to form 2D materials composites we have to first disperse them chemically in solution. MoS2 and WS2 powders were oversaturated in N-Methyl-2-pyrrolidone (NMP) solution at 37.5 mg/mL and sonicated at room temperature (RT) for sonication times ranging from 30 minutes to close to 24 hours. After solution processing, the samples with the 2D flakes were transferred to an Isopropyl Alcohol (IPA) bath for particle size distribution analysis. We have observed significant changes in particle size distribution spanning two orders of magnitude as a function of the sonication conditions. Specifically, the observed changes in particle size distribution for MoS2 and WS2 powders ranged from 44 microns down to 0.409 microns, and 148 microns down to 0.409, respectively, as compared to the untreated materials. Structural analysis was conducted using the SEM and X-Ray diffraction. The structural analysis using the SEM revealed morphological signatures between the two materials, where the MoS2 flakes had a randomly oriented distribution with occasional triangular flakes. In the case of the WS2, regardless of the sonication conditions, the WS2 flakes seemed to have a characteristic 120° angular distribution at the vertices, representing a rhombus with concave edges. The XRD analysis showed a minute shift in the characteristic peaks that maybe due to strain-induced effects as a result of the solution processing. Optical characterization of the materials was also conducted using Raman Spectroscopy to validate the average layer number resulting from the solution dispersions and the spatial and compositional uniformity of the two material samples.